Among Ectasia Patients with Coexisting Coronary Artery Disease, TIMI Frame Count Correlates with Ectasia Size and Markis Type IV Is the Commonest - Hasahya Tony; Kai Meng; Bangwei Wu; Qiutang Zeng (Cardiology Research and Practice, 2015)
Background. Coronary artery ectasia (CAE) occurs in 0.3 to 5.3% of patients undergoing coronary angiography. TIMI frame count (TFC) is an index of coronary flow that correlates with flow velocity. In ectasia patients, there is delayed coronary flow with increased TFC. Methods. We evaluated angiograms of 789 patients for presence of CAE, coronary artery disease (CAD), and Markis type of CAE. We measured ectasia size and length and their correlation with TFC in ectatic right coronary arteries (RCA) of patients with CAE and CAD. Results. 30 patients had CAE (3.8%). Of these 16.7% had isolated CAE, while 83.87% had CAE and CAD. Among CAE and CAD patients, the RCA was most involved (70.4%), and Markis type IV CAE was the commonest (64%). In isolated CAE, the RCA, LAD, and LCx were equally involved (33.3%). Patients with CAE and CAD had significantly higher TFC compared to controls, P=0.035. There was a positive correlation of moderate strength, between ectasia size and TFC, r(17) = 0.598, P=0.007. Ectasia length was not significantly correlated with TFC, rho (17) = 0.334, P=0.163. Conclusion. Among patients undergoing angiography, CAE has a prevalence of 3.8% and Markis type IV is the commonest. Larger ectasias are associated with slower coronary flow.